2014
DOI: 10.1007/s11090-014-9538-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Reactive Hydroxyl Radical Species Inside the Biosolutions During Non-thermal Atmospheric Pressure Plasma Jet Bombardment onto the Solution

Abstract: Non-thermal atmospheric pressure plasma jet could generate various kinds of radicals on biosolution surfaces as well as inside the biosolutions. The electron temperature and ion density for this non-thermal plasma jet have been measured to be about 0.8*1.0 eV and 1 9 10 13 cm -3 in this experiment, respectively, by atmospheric pressure collisional radiative model and ion collector current. In this context, the hydroxyl OH radical density inside the biosolutions has been also investigated experimentally by ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 20 publications
0
55
0
1
Order By: Relevance
“…The formation of O 2 and H 2 molecules was discovered as well. In study [25], the formation of Á OH radicals in a liquid phase was detected by absorption method under the action of argon plasma jet onto water surface. In study [26], Á OH radicals were monitored indirectly using the fluorescent properties of hydroxyterephthalic acid formed in the reaction of terephthalic acid with Á OH radicals.…”
Section: Kinetic Model Kinetic Model For Aqueous Solutionsmentioning
confidence: 99%
“…The formation of O 2 and H 2 molecules was discovered as well. In study [25], the formation of Á OH radicals in a liquid phase was detected by absorption method under the action of argon plasma jet onto water surface. In study [26], Á OH radicals were monitored indirectly using the fluorescent properties of hydroxyterephthalic acid formed in the reaction of terephthalic acid with Á OH radicals.…”
Section: Kinetic Model Kinetic Model For Aqueous Solutionsmentioning
confidence: 99%
“…The gas residence time in study [5] was 6 min, whereas in our study it was *17 s. Undoubtedly, the increase in gas flow rate can lead to a gas cooling and to water molecules concentration and other neutral species dropping. The passing OH concentration through the maximum under the increase in a gas flow rate was observed in study [43].…”
Section: Resultsmentioning
confidence: 77%
“…The obtained experimental data has shown that at the pH =11, the TNR degradation efficiencies and reaction rate are higher at pH= 11.Due to that at this pH, the ozone resulting in plasma discharge is easily converted in hydroxyl radical. This radical is more reactive in alkaline medium the in acid or neutral one that has suggested in [10].…”
Section: Influence Of Ph On the Tnr Degradationmentioning
confidence: 64%